Utilization of UI Park as an Ecotourism Destination on Weekends - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Rachman, Anita; Rachmawati, Kurnia (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Ecotourism is a tourism sector that has the potential to support the national economy, ecotourism can also be utilized by local governments to increase their own local income. UI Park, located in the University of Indonesia area, has great potential as an ecotourism destination on weekends. As a vast green area and has a rich biodiversity, Taman UI offers the potential for a refreshing and educational nature tourism experience for the local community and tourists. This paper aims to analyze and explain various aspects related to the use of UI Park as an ecotourism destination on weekends. In this paper, we will examine the factors that affect the tourist attraction of Taman UI, the potential of existing biodiversity, the needs of visitors, and development strategies that can be done to improve the utilization and sustainability of Taman UI as a sustainable ecotourism destination.